Jouissance : a Lacanian concept - Braunstein, Néstor A. (SUNY Series, Insinuations: Philosophy, Psychoanalysis, Literature Ser., 2020)
"Whether inscribed within the context of capitalist or neoliberal logic and its imperative to "enjoy," as a critique of all forms of hetero-normativity, a liberating force in a positive reading of biopolitics, the point of inflection in the ethics of psychoanalysis, or articulated in the knot of the sinthome, jouissance is either the diagnosis, response, or solution for a wide range of contemporary discontents. Why does jouissance occupy such a central place in contemporary psychoanalytic discourse? What is jouissance the name for? Originally published in Spanish in 1990 and translated into French and Portuguese, with multiple reprints in all three languages, Jouissance: A Lacanian Concept addresses both theoretical and clinical applications, and includes discussions of key terms in Lacan's grammar in order to provide a comprehensive overview of this elusive concept. In addition, Néstor A. Braunstein discusses jouissance in relation to other key figures in the fields of psychoanalysis and philosophy, and turns to literary texts and queer theory to further explore the implications of these interpretations for contemporary cultural debates"--